Neurodevelopmental evaluation strategies for children with congenital heart disease aged birth through 5 years: recommendations from the cardiac neurodevelopmental outcome collaborative. (4th November 2020) - Ware, Janice; Butcher, Jennifer L.; Latal, Beatrice; Sadhwani, Anjali; Rollins, Caitlin K.; Brosig Soto, Cheryl L.; Butler, Samantha C.; Eiler-Sims, Patricia B.; Ullman Shade, Catherine V.; Wernovsky, Gil
Abstract: This paper provides specific guidelines for the neurodevelopmental evaluation of children aged birth through 5 years with complex congenital heart disease. There is wide recognition that children with congenital heart disease are at high risk for neurodevelopmental impairments that are first apparent in infancy and often persist as children mature. Impairments among children with complex congenital heart disease cross developmental domains and affect multiple functional abilities. The guidelines provided are derived from the substantial body of research generated over the past 30 years describing the characteristic developmental profiles and the long-term trajectories of children surviving with complex congenital heart conditions. The content and the timing of the guidelines are consistent with the 2012 American Heart Association and the American Academy of Pediatrics scientific statement documenting the need for ongoing developmental monitoring and assessment from infancy through adolescence. The specific guidelines offered in this article were developed by a multidisciplinary clinical research team affiliated with the Cardiac Neurodevelopmental Outcome Collaborative, a not-for-profit organisation established to determine and implement best neurodevelopmental practices for children with congenital heart disease. The guidelines are designed for use in clinical and research applications and offer an abbreviated core protocol and an extended version that expands the scope of the evaluation. The guidelines emphasise the value of early risk identification, use of evidence-based assessment instruments, consideration of family and cultural preferences, and the importance of providing multidimensional community-based services to remediate risk.